- #1

- 6

- 0

## Main Question or Discussion Point

I was asked to use a laplace transform to solve d^2x/dt^2 - 3(dx/dt) - 10x = e^-t

with the initial conditions x(0) = 0 and x'(0) = 0

I got down to (s^2)x(s) - sx(0) - x'(0) - 3(sX(0) - x(0)) - 10X =1/(s+1)

I tried plugging in the initail conditions and didnt get the answer I was supposed to, think I have gone wrong somewhere if someone can help me out

with the initial conditions x(0) = 0 and x'(0) = 0

I got down to (s^2)x(s) - sx(0) - x'(0) - 3(sX(0) - x(0)) - 10X =1/(s+1)

I tried plugging in the initail conditions and didnt get the answer I was supposed to, think I have gone wrong somewhere if someone can help me out